Gender and competitiveness when earning for others: Experimental evidence and implications for sponsorship - Barrymore, Nathan; Dezső, Cristian L.; King, Benjamin C. (Strategic Management Journal, 2022)
Abstract Research Summary Career paths depend not only on individuals' own competitiveness but also on the competitiveness of others in a position to advocate for them. In this article, we study competitiveness when rewards accrue to another individual. In particular, we ask how female and male managers' competitiveness changes when rewards from competition accrue to their female or male protégés, relative to when they accrue to themselves. Using an experimental approach, we find that when rewards accrue to protégés, male and female managers are equally competitive because female managers increase their competitiveness. However, male managers compete more for male rather than female protégés. This gap disappears when male managers know their protégés' risk preferences, suggesting a novel intervention to ensure equity in the sponsorship process. Managerial Summary Sponsorship is key to individuals' career development and firms' human capital strategy. In this experimental study simulating an organizational setting, we investigate one aspect of sponsorship and ask whether managers' and protégés' genders affect managers' willingness to compete on behalf of their protégés. We find that when the rewards from competition accrue to protégés, female managers increase their competitiveness and eliminate the gender competitiveness gap present when rewards accrue to managers themselves. This suggests that, from a competitiveness standpoint, female and male managers are equally strong sponsors. However, male managers compete more for male, relative to female, protégés. This gap disappears when male managers have information about protégés' risks preferences, suggesting a novel approach that organizations can implement to reduce discrimination in sponsorship.